2022
DOI: 10.24093/awej/covid2.9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Saudi Female Students’ Familiarity of Word-Formation Processes Related to COVID-19 Pandemic Terminology

Abstract: With the outbreak of the COVID-19 pandemic, new words appeared in English. EFL learners need to learn the new words. Learners depend on many strategies to help them learn new terms. Investigating this topic is significant because it will contribute to the knowledge of teaching and learning new words that appeared rapidly and suddenly. This study aims to investigate the acquisition of word-formation processes related to COVID-19 terms. The research seeks to answer two questions: (1) Are Saudi female EFL learner… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The results revealed that both data analysis techniques have successfully provided support to all the hypothetical and assumed Arab World English Journal www.awej.org ISSN: 2229-9327 140 relationships of the research model. Alqahtani (2022) conducted a study that examined Saudi female students' awareness of word-formation procedures about the terminology of unknown coronavirus. The study attempts to study the acquisition of word-formation procedures appertaining to the terms of novel coronavirus pneumonia.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The results revealed that both data analysis techniques have successfully provided support to all the hypothetical and assumed Arab World English Journal www.awej.org ISSN: 2229-9327 140 relationships of the research model. Alqahtani (2022) conducted a study that examined Saudi female students' awareness of word-formation procedures about the terminology of unknown coronavirus. The study attempts to study the acquisition of word-formation procedures appertaining to the terms of novel coronavirus pneumonia.…”
Section: Previous Studiesmentioning
confidence: 99%